Debris flow disaster in Larcha, upper Bhotekoshi Valley, central Nepal - Adhikari, Danda P; Koshimizu, Satoshi (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.89-90